Meningkatkan Motivasi dan Kinerja SDM Pelaku UMKM dengan Gaya Kepemimpinan Melayani - Grace Maria Fitricia; Yadi Fakhruzein Terang Jaya (FKIP, Universitas Palangka Raya, 2025)
Human resources are one of the main factors determining the effectiveness and efficiency of an organization which results in the achievement of organizational goals as an important resource beside capital resources, technology and equipment. Human resources who can process the resources owned by the organization effectively and efficiently will be able to achieve organizational goals as expected and can survive in business competition. To get the best human resources, the role of leadership is really important. In this community service activity, socialization was held to manage human resources,especially human resources in MSMEs with a servant leadership style for the purpose to manage human resources by empowering them who work in MSMEs to be more empowered and produce better performance to achieve organizational’s goal.